A Successful Repair of Ruptured Prostatic Part of Urethra: A Case Report - Hamal, B K; Joshi, Amit (Medical Journal of Shree Birendra Hospital, 2002)
A Successful Repair of Ruptured Prostatic Part of Urethra: A Case Report